![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^{20}=x\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
b) \(x^6:x^3=125\)
\(\Leftrightarrow x^{6-3}=125\)
\(\Leftrightarrow x^3=125\)
\(\Leftrightarrow x^3=5^3\)
\(\Leftrightarrow x=5\)
c) \(4x^3+12=120\)
\(\Leftrightarrow4x^3=120-12\)
\(\Leftrightarrow4x^3=108\)
\(\Leftrightarrow x^3=27\)
\(\Leftrightarrow x^3=3^3\)
\(\Leftrightarrow x=3\)
d) \(x^{10}=x^1\)
\(\Leftrightarrow x^{10}=x\)
\(\Rightarrow\orbr{\begin{cases}x=1\\x=0\end{cases}}\)
e) \(\left(2x-15\right)^5=\left(2x-15\right)^3\)
\(\Leftrightarrow\left(2x-15\right)^5-\left(2x-15\right)^3=0\)
\(\Leftrightarrow\left(2x-15\right)^3\left[\left(2x-15\right)^2-1\right]=0\)
\(\Rightarrow\orbr{\begin{cases}\left(2x-15\right)^3=0\\\left(2x-15\right)^2-1=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}2x-15=0\\\orbr{\begin{cases}2x-15=1\\2x-15=-1\end{cases}}\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{15}{2}\\\orbr{\begin{cases}x=8\\x=-7\end{cases}}\end{cases}}\)\(\Rightarrow2x-15=0\)hoặc \(2x-15=1\) hoặc \(2x-15=-1\)
\(\Rightarrow x=\frac{15}{2}\)hoặc \(x=8\)hoặc \(x=7\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (2x-6)3 = (2x-6)2018
=> (2x-6)3 - (2x-6)2018 = 0
(2x-6)3.[1-(2x-6)2015 ] = 0
=> (2x-6)3 = 0 =>...
1 - (2x-6)2015 = 0 => (2x-6)2015 = 1 => ...
b) (2x-1)3 = 27 = 33
=> 2x - 1 = 3
=> ...
c) (x + 1) + (x+2) + (x+3) + ...+ (x+100) = 5750
x.100 + (1+2+3+...+100) = 5750
x.100 + [(1+100).100:2] = 5750
x.100 + 5050 = 5750
x.100 = 700
x = 7
![](https://rs.olm.vn/images/avt/0.png?1311)
a)27^6:9^3=(3^3)^6:(3^2)^3=3^18:3^6=3^12
b)4^20:2^15=(2^2)^20:2^15=2^40:2^15=2^25
a) 27^6 : 9^3
= ( 3^3)^6 : ( 3^2)^3
= 3^18 : 3^6
= 3^12
b) 4^20 : 2^15
= ( 2^2)^20 : 2^15
= 2^40 : 2^15
= 2^25
d) 64^4 x 16^5 : 4^20
= (4^3)^4 x (4^2)^5 : 4^20
= 4^12 x 4^10 : 4^20
= 4^22 : 4^20
= 4^2
2x + 15 = -27
2x = (-27) - 15
2x = -42
x = (-42) : 2
x = -21
2x + 15 = -27
2x = (-27) - 15
2x = -42
x = (-42) : 2
x = -21